Multiplicity in the digital era: Processing and learning from multiple sources and modalities of instructional presentations. (October 2018) - Mason, Lucia
Abstract: This commentary on the five articles in the Special Issue will first introduce research issues regarding the processing of multiple texts in order to outline the scenario in which the contributions are placed. Then, in the light of the need to move beyond multiple text processing in the digital era, the commentary will illustrate how the five articles contribute to finding answers to some important open questions, furthering our understanding of the processing of instructional materials which feature multiple sources, multiple symbol systems, and multiple modalities of presentation. Finally, the commentary will suggest some issues arising from the outcomes of the studies in this Special Issue, which are worthy of further exploration. Highlights: The five papers move beyond multiplicity confined to texts. Multi-source and multiple-modal processing of information is addressed. Processing of digital and printed texts, texts and videos, and texts and pictures is examined.